2012
DOI: 10.2147/ijn.s27709
|View full text |Cite
|
Sign up to set email alerts
|

Improved drug loading and antibacterial activity of minocycline-loaded PLGA nanoparticles prepared by solid/oil/water ion pairing method

Abstract: Background: Low drug entrapment efficiency of hydrophilic drugs into poly(lactic-co-glycolic acid) (PLGA) nanoparticles is a major drawback. The objective of this work was to investigate different methods of producing PLGA nanoparticles containing minocycline, a drug suitable for periodontal infections. Methods: Different methods, such as single and double solvent evaporation emulsion, ion pairing, and nanoprecipitation were used to prepare both PLGA and PEGylated PLGA nanoparticles. The resulting nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…PLGA provides a wide range of advantages, such as a smaller particle size that facilitates penetration into the cells, higher entrapment efficiency for increased drug release, lower minimum inhibitory concentration, and minimum bacterial concentrations, meaning that a better antibacterial activity was achieved with a smaller amount of drug (30,31). The present study provided evidence that a PLGA showed an interaction with bone repair when it was used as a filling material in bone defects.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…PLGA provides a wide range of advantages, such as a smaller particle size that facilitates penetration into the cells, higher entrapment efficiency for increased drug release, lower minimum inhibitory concentration, and minimum bacterial concentrations, meaning that a better antibacterial activity was achieved with a smaller amount of drug (30,31). The present study provided evidence that a PLGA showed an interaction with bone repair when it was used as a filling material in bone defects.…”
Section: Discussionmentioning
confidence: 54%
“…The author explained this result by the high concentration (10%) of doxycycline in the preparation. However, the present study showed positive results with this concentration, probably due to the drug administration by the vehicle-PLGA, which decreased the high concentration and reduced contact between the tissue and drugs (30,31). The 10% of doxycycline has been used in several commercially available agents with positive results in bone formation (38) and alendronate can be applied topically in lower doses to locally inhibit bone resorption (39).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nanoparticles synthesize with polymers such as Poly (Lactic co-Glycolide Acid) were reported to have a high EE due to its molecular structure that is associated to its active sites [17]. An EE of 47.6% and 38.9% for cinnamon bark extract loaded in PLGA-50 and PLGA-65 NP, respectively was reported by Hill et al [18].…”
Section: Introductionmentioning
confidence: 91%
“…36,37 The molecular weight of the polymer can be varied to marginally control the release of payload. 35,36,38 Coating the PLGA surface with hydrophobic materials, like gelatin or chitosan 34 , can decrease the initial drug burst and extend the release period. The rapid degradation of polyester products occurs in microenvironments with a low pH (1.5 – 3.6), 39,40 which can be problematic when the therapeutic payload is denatured in parallel.…”
Section: Advances In Polymer Chemistry and Nanoparticle Delivery Formentioning
confidence: 99%